The Role of Metal Ions in Fungal Organic Acid Accumulation - Levente Karaffa; Erzsébet Fekete; Christian P. Kubicek (Microorganisms, 2021)
Organic acid accumulation is probably the best-known example of primary metabolic overflow. Both bacteria and fungi are capable of producing various organic acids in large amounts under certain conditions, but in terms of productivity-and consequently, of commercial importance-fungal platforms are unparalleled. For high product yield, chemical composition of the growth medium is crucial in providing the necessary conditions, of which the concentrations of four of the first-row transition metal elements, manganese (Mn2+), iron (Fe2+), copper (Cu2+) and zinc (Zn2+) stand out. In this paper we critically review the biological roles of these ions, the possible biochemical and physiological consequences of their influence on the accumulation of the most important mono-, di- and tricarboxylic as well as sugar acids by fungi, and the metal ion-related aspects of submerged organic acid fermentations, including the necessary instrumental analytics. Since producing conditions are associated with a cell physiology that differs strongly to what is observed under “standard” growth conditions, here we consider papers and patents only in which organic acid accumulation levels achieved at least 60% of the theoretical maximum yield, and the actual trace metal ion concentrations were verified.